2001
DOI: 10.1159/000045901
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Salivary Epidermal Growth Factor in Peptic Ulcer Diseasein Hemodialysis Patients

Abstract: Background/Aims: Hemodialysis (HD) patients are prone to developing peptic ulcers. However, of all the risk factors associated with peptic ulcers, none have been shown to be more prevalent in HD patients than in the general population. However, salivary epidermal growth factor (EGF) may play a role in peptic ulcer diseases. Methods: Salivary EGF levels and bioactivities were assayed in 47 maintenance HD patients and 30 normal controls, and the molecular weights of EGF were assessed using high-performance liqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Another view is that the submandibular gland derived factors participate in "set point" determination that impacts on the outcome of an injury or inflammation [140,141]. Supporting this later view are the observations that removal of the submandibular glands is associated the aggravation of a numerous physiological parameters, including acid induced esophagitis [142], the harmful effects of epinephrine on the heart [143], induction and maintenance of optimal immunity in the stomach [144], growth and metabolic function of the liver [145], inflammatory responses to bacterial endotoxins [145][146][147], maintenance of body temperature [140], optimal reproductive function [148], and the healing of oral [149] and peripheral [150] wounds, and esophageal [151] and gastric ulcers [152,153].…”
Section: Salivary Gland Factorsmentioning
confidence: 99%
“…Another view is that the submandibular gland derived factors participate in "set point" determination that impacts on the outcome of an injury or inflammation [140,141]. Supporting this later view are the observations that removal of the submandibular glands is associated the aggravation of a numerous physiological parameters, including acid induced esophagitis [142], the harmful effects of epinephrine on the heart [143], induction and maintenance of optimal immunity in the stomach [144], growth and metabolic function of the liver [145], inflammatory responses to bacterial endotoxins [145][146][147], maintenance of body temperature [140], optimal reproductive function [148], and the healing of oral [149] and peripheral [150] wounds, and esophageal [151] and gastric ulcers [152,153].…”
Section: Salivary Gland Factorsmentioning
confidence: 99%
“…In addition, it is evident that the EGFR signaling pathways are regulated by sex hormones [1921]. Studies have shown sex difference of salivary and tear EGF levels [22, 23], as well as the EGF effects in ulcer healing [24]. Moreover, sex-specific associations of EGF polymorphisms with phenotypes have been found in schizophrenia [25, 26].…”
Section: Introductionmentioning
confidence: 99%